SISTEM KOORDINASI UNTUK PENGAMBILAN KEPUTUSAN PADA ROBOT SEPAKBOLA BERODA - Zaky Wafa Albahari; Akhmad Musafa; Indra Riyanto; Sujono Sujono (MAESTRO, 2020)
Wheeled robot soccer matches have problems, one of which is the ability to coordinate. Because in a one-wheeled soccer robot match a team consists of several robots, then cohesiveness is the deciding factor to produce a good game. To produce good cohesiveness, coordination between robots is needed. In this final project a coordination system for decision making in a wheeled soccer robot team is designed. This research was conducted by simulating three robot units, one coordinator robot unit and two member robot units, with the addition of 3 silent robot opponents. The main concept of this research is the action taken by each robot in the team is the result of the decision of the coordinating robot. Robot members have two jobs in the team, namely sending all match situation data read by the sensor to the coordinating robot, and executing commands for each robot that is determined by the coordinating robot. The coordinating robot gives commands to each robot based on all match condition data collected by all robots. To avoid other robots in the team when moving, sin and cos rules are used. Meanwhile, to avoid opposing robots as well as path planning using Dijkstra’s Algorithm. The results of this study the robot managed to move in a coordinated manner that is only moving the robot that is most suitable for action. While the other robots are prepared to wait for conditions suitable for him to take action. Besides robots can also move without crashing into other robots both robots in the team and the robot opponent. In various cases carried out in testing, the robot takes from 3 to 5 seconds to do its job.